2020
DOI: 10.21638/spbu18.2020.307
|View full text |Cite
|
Sign up to set email alerts
|

Intangible-driven performance: Two decades searching for the Philosopher's Stone

Abstract: The study offers a structural literature review on the twenty years the evolution of the fast-growing research topic of intellectual capital (IC) and intangible-driven performance. Despite a rather short independent history, the IC concept has undergone a substantial transformation, bringing to the discussion vast empirical and methodological literature. Several endeavors carrying out literature review studies could only partially satisfy the needs of the systematization of the relevant research. Hence, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…More than three persons co-author a relatively large proportion of papers (28.72%). This fact is consistent with the increasing trend in the number of co-authors that have been reported in the economic and business literature [Kuld, O'Hagan, 2018;Rath, Wohlrabe, 2016;Shakina, Molodchik, Parshakov, 2020].…”
Section: Sample Descriptionsupporting
confidence: 89%
“…More than three persons co-author a relatively large proportion of papers (28.72%). This fact is consistent with the increasing trend in the number of co-authors that have been reported in the economic and business literature [Kuld, O'Hagan, 2018;Rath, Wohlrabe, 2016;Shakina, Molodchik, Parshakov, 2020].…”
Section: Sample Descriptionsupporting
confidence: 89%
“…Therefore, it is reasonable to consider a set of corporate relations as an important and valuable asset. This is realized within the concept of "Intellectual Capital" (IC) which became very popular in theoretical and empirical research in the last two decades (Shakina, Molodchik and Parshakov, 2020). This concept implies that a significant share of firm capital is intangible.…”
Section: Introductionmentioning
confidence: 99%